Effects of Arak Bali Administration on Spermatozoa DNA Fragmentation and Testosterone Level of Rats (Rattus norvegicus) - Hayati, Alfiah; Winarni, Dwi; Antari, Ni Wayan Sukma; Resita, Inne Ninda; Fauziah, Erlyn Nurul (Folia Medica Indonesiana, 2018)
This study aimed to determine the effects of arak bali on the fragmentation of spermatozoa and testosterone in rats (Rattus norvegicus). This study used 24 rats (170-200 g), divided into four groups: one control and three treatments (receiving arak bali containing 40% alcohol as much as 0.1 and 0.5 mL and synthetic alcohol (40%) as much as 0.1 mL, for 45 days). The observation of DNA fragmentation was done using acridine orange staining and the measurement of testosterone level used ELISA method. The results showed that the provision of arak bali in experimental animals increased the occurrence of spermatozoa DNA fragmentation. The higher the volume of arak bali given, the higher the fragmentation of spermatozoa DNA. The administration of arak bali also decreased testosterone level. The higher the volume of arak bali given, the lower the rats' testosterone level.